2019
DOI: 10.1371/journal.pone.0213808
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing naked oat (Avena nuda L.) productivity with minimal indirect nitrogen loss and maximum nitrogen use efficiency through integrated use of different nitrogen sources

Abstract: Oat (Avena nuda L.) is a nutritious grain crop, rich in dietary fibers and phytochemicals. Application of efficient nitrogen (N) sources and dose is very important to obtain higher crop productivity and to achieve environmental sustainability. The exploitation of natural beneficial microbes and organic nitrogen in combination with chemical nitrogen would be effective to boost soil N for plant uptake. Hence, a field experiment was conducted during 2016 and 2017 with the aim to ameliorate the use of chemical N (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 75 publications
(89 reference statements)
0
5
0
Order By: Relevance
“…Contrary to these findings, long-term results indicated that grain number per spike was the main factor that affected grain yield in lower mean temperature growing season while 1000-grain weight was the main factor that influenced grain yield in growing seasons with higher mean temperature, respectively. The reason might be that water was the first limiting factor determining the grain yield formation and could affect the contributions of yield components to yield [50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to these findings, long-term results indicated that grain number per spike was the main factor that affected grain yield in lower mean temperature growing season while 1000-grain weight was the main factor that influenced grain yield in growing seasons with higher mean temperature, respectively. The reason might be that water was the first limiting factor determining the grain yield formation and could affect the contributions of yield components to yield [50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…At harvesting, An area of 100 cm 2 was selected in duplicate (as technical replicates) from every biological replicate, 10 plants from each technical replicate were selected for the determination of panicle/spike length, number of grains per panicle/spike of rice/wheat and the data were averaged to serve as one biological replicate [31,53]. For paddy/grain and straw yield, three samples (1 m 2 ) were manually harvested and threshed to measure grain and straw weight.…”
Section: Growth and Yield Attributesmentioning
confidence: 99%
“…INM options References Plant height 75% RDF + 5t FYM/ha + 20 kg S/ha [15] 50% N through chemical source + 50% N through organic and microbial fertilizer sources [16] 120 kg N/ha + vermicompost @ 10t/ha + seed inoculation through Azotobacter [17] Plant height and leaf: stem Application of green manure along with 25% nitrogen through FYM and 50% of RDF through inorganic sources Application of green manure along with 25% nitrogen through FYM and 50% of RDF through biofertilizer [18] Plant height, tiller number/plant, tiller number/m 2 , number and area of leaves/plant and dry matter/tiller FYM or poultry manure as substitute of certain part of RDF [19] Plant height, tiller numbers, tiller fresh and dry weights and leaf area/plant 50% N through urea and 50% N through poultry manure [20] Crop growth rate 50% inorganic and 50% organic (FYM) or 75% inorganic and 25% organic (FYM) sources of nutrients [21] Plant height, leaf: stem, shoots/metre and leaves/plant 50% RDF + vermicompost and FYM each @ 5t/ha [22] Plant height, shoots/metre row length 100% RDF + 5 t vermicompost/ha [23] Plant height, leaf and tiller numbers 100% RDF + vermicompost @ 5t/ha/FYM @ 10 t/ha + ZnSO 4 @ 15 kg/ha [7] Plant height and tiller numbers 50% RDF + 10t FYM/ha + seed inoculation through PSB and Trichoderma [9], [24] Plant height, leaf area index and dry matter 75% RDF along with vermicompost and seed inoculation through Azotobacter [25] Plant height, leaf area index, root length and weight 75% N through urea + 25% N through vermicompost [1] Dry matter accumulation and crop growth rate [26] [15] 50% RDF + vermicompost and FYM each @ 5t/ha.…”
Section: Growth Attributes Influencedmentioning
confidence: 99%
“…[16] observed that nutrient use efficiencies such as partial factor productivity (PFP), agronomic nitrogen use efficiency (ANUE), apparent nitrogen recovery efficiency (ANRE) of naked oat (Avena nuda L.) were significantly higher under application of 50% N through chemical source along with 50% N through organic and microbial fertilizer sources which was closely followed by application of 75% N through chemical source along with 25% N through organic and microbial fertilizer sources over control and 100% N through chemical source They, however, indicated that, physiological nitrogen use efficiency (PNUE) remained statistically indifferent irrespective of treatments. In their study, Khan et al (2019) [16] further noticed that among various INM options, application of 50% N through chemical source along with 50% N through organic and microbial fertilizer sources exhibited better soil respiration (CO 2 ) rate, enzymatic activities (acid phosphatase, dehydrogenase, arylsulphatase, BAA-protease, β-glucosidase) over control and 100% N through chemical source. Oat seed inoculation through biofertilizers has been also found to improve soil biological health.…”
Section: Nutrient Use Efficiency and Soil Biological Healthmentioning
confidence: 99%
See 1 more Smart Citation